Australia-Taiwan First Nations Art Exchange 2023 - Short Documentary - Hart, Phoebe; McIntyre, Sophie; Watan, Baunay; Quadrio, Mandy; Ah Kee, Vernon; Taru, Yuma; Lin, Anchi (YouTube, 2024)
This short documentary is based on a pilot project - when four Indigenous artists visited Taiwan and Australia for 10 days in June and July 2023 to undertake field research, led by Dr. Sophie McIntyre and Dr. Fang Chun-wei. It was the first time most of these artists had travelled to Taiwan and Australia, and it was also the first time they met other project participants face-to-face. During these initial visits, each artist delivered introductory talks and workshops in Taipei and Taitung focusing on their art practices. They also visited artist studios, galleries, museums and met with curators, communities and government officials. These four artists were also involved in Stages 1 and 2 of this ongoing Australia-Taiwan First Nations Art Exchange project which comprises an international symposium (2021, https://research.qut.edu.au/cpfsi/events/grounded-in-place-symposium/) and publication (Pacific Arts, UCLA, 2022, https://escholarship.org/uc/item/73k4s2c9). These field trips were funded by the Ministry of Culture Taiwan. This short video draws on archival footage taken during these visits, mostly by Baunay Watan, an amateur filmmaker and husband of Atayal artist Yuma Taru, and interviews filmed in Australia after the pilot project had concluded by Dr Phoebe Hart.